Indigenous Knowledge and Socio-Cultural Learning: The Educational Meaning of the Meruba Ritual among Dayak Krio Community - Iwan Ramadhan; Figur Adhiyakam; Martono Martono; Muhammad Agus Hardiansyah; Yudhistira Oscar Olendo (Jurnal Mamangan, 2025)
This study explores the educational values embedded in the Meruba ritual of the Dayak Krio community, focusing on its role in supporting socio-cultural learning practices based on indigenous knowledge. The core issue addressed is how the Meruba ritual serves as a medium for transmitting religious, social, and moral values across generations, thereby strengthening social cohesion and cultural sustainability. The objective of this research is to analyze the procession and educational meanings of the Meruba ritual and emphasize its relevance within the context of multicultural education. Utilizing the theoretical framework of socio-cultural learning, which views social interaction as the foundation of the learning process, and the concept of indigenous knowledge, which explains how local knowledge systems are transmitted through cultural practices, this study positions the Meruba ritual as a vehicle for knowledge transfer encompassing spiritual, social, and moral dimensions. The research employs a qualitative approach, using participatory observation, in-depth interviews, and document analysis conducted on June 24–25, 2024. These methods aim to obtain a comprehensive understanding of the ritual's implementation and the educational values contained within it. The findings reveal that the Meruba ritual consists of three stages: the initial procession, the core procession, and the closing procession. Each stage incorporates specific educational dimensions, including religious values that reinforce spiritual beliefs and ancestral reverence, social values that foster solidarity and collective participation, and moral values that instill ethics and social responsibility in younger generations. The Meruba ritual is not merely a cultural practice but also serves as an effective medium for socio-cultural learning grounded in indigenous knowledge. The novelty of this study lies in its holistic approach to understanding Meruba as an educational praxis that bridges indigenous knowledge with multicultural education, offering significant contributions to the development of learning models based on local wisdom.